How End-of-Life Blogs Re-Affirm the “Power to be Oneself” - Green, Gill (Frontiers in Sociology, 2022)
Powerlessness generally denotes loss of control and may be experienced among those with a terminal diagnosis and, as such, empowerment is a dominant discourse in end-of-life policy in the western Anglo-Saxon world. This paper analyzes thematically blogs authored by three people with a terminal diagnosis to examine the ‘power to be oneself’, a concept which was identified in the ‘Ethics of Powerlessness’ project conducted in the UK. The analysis demonstrates that the bloggers assert the ‘power to be themselves’ which is expressed in three principal ways. Firstly, through assertion of agency to promote self-affirmation and control. Secondly, through claiming a ‘moral authority’ expressed by providing advice not just on illness and death but also on how life should be lived. Thirdly, through discussing ideas about the future and creating a legacy. The blogs are a mechanism used to express and reinforce self-identity and to carve out a ‘sacred space’ between life and death to nurture personal change and to project this onto a public arena. This analysis demonstrates the key role patient empowerment plays in constructing an identity with a terminal diagnosis, an element that is often overlooked in end-of-life policy.